3-Phenylphosphaprolines – Synthesis, structure and properties of heterocyclic α-phosphanyl amino acids. (7th July 2017) - Basvani, Kaleswara R.; Kindermann, Markus K.; Frauendorf, Holm; Schulzke, Carola; Jones, Peter G.; Heinicke, Joachim W.
Graphical abstract: A synthetic route to novel heterocyclic α-phosphanyl amino acids via [4+1]-cyclocondensation is presented. Reaction monitoring and multinuclear NMR data characterize key intermediates, diastereoisomer composition, solution structure, slow isomerization and for the 2-phenyl compound thermal decarboxylation. XRD analyses prove preference of trans -isomers in the crystals. Preliminary catalytic tests hint at possible use in transition metal catalysis. Abstract: "Phenylphosphaprolines", containing trivalent phosphorus within the five-membered ring of proline, were synthesized by cyclocondensation of 2-phenylphosphanyl ethylamines1a, b with equimolar amounts of glyoxylic acid hydrate (GAH) or pyruvic acid in diethyl ether or 1, 4-dioxane. Reaction monitoring revealed primary formation of acyclic intermediates that then converted more (1a ) or less (1b ) rapidly to the phosphanyl amino acids cis / trans -2a, b or cis / trans -4a, b . Ammonium-ethylphosphonium-bis(glycolate) impurities, e.g.3b, were formed when an excess of GAH was applied. The conversion of1a with phenylformic acid via the acyclic precursors5a and6a to the heterocyclic product cis / trans -7a was very slow, whereas heating of the mixture in 1, 4-dioxane proceeded with decarboxylation to cis / trans -8a . The structures and diastereoisomer ratios of all new compounds were determined by 1 H, 31 P and 13 C solution NMR spectra. The cis / trans -ratio of2a depends on the synthetic route, i.e. addition of the phosphanylethyl amine1a to GAH (acidic medium) or of GAH to1a (basic medium). Furthermore, this ratio changed slowly during storage of the solution of2a in CD3 OD or methanol, indicating ring-opening ring-closure reactions and lower kinetic stability than for proline. XRD analyses established the structures of trans -2a and likewise of trans -4a and trans -8a, which from concentrated solutions crystallized in pure form.